2008
DOI: 10.1002/anie.200800255
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Solvent‐Induced Homochirality by the Confinement of Achiral Molecules Against a Solid Surface

Abstract: One hand mapping: By means of scanning tunneling microscopy, solvent‐induced homochirality is shown to emerge in self‐assembled monolayers of achiral molecules at the liquid–solid interface (see picture). The chirality of the solvent directs the macroscopic chirality of the monolayer. The dynamics of the monolayer structure as it evolves towards homochirality are probed by time‐dependent measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
59
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 39 publications
8
59
0
Order By: Relevance
“…Using chiral solvents, excess of CW or CCW pinwheels in monolayers of achiral oligophenylene derivatives, similar to those shown in Fig. 19, was reported [164]. Using these achiral oligophenylenes and dibenzoyl tartaric acid as chiral auxiliaries in the achiral solvent, the same effect was observed [165].…”
Section: Diastereomers and Diastereomeric Recognitionsupporting
confidence: 70%
“…Using chiral solvents, excess of CW or CCW pinwheels in monolayers of achiral oligophenylene derivatives, similar to those shown in Fig. 19, was reported [164]. Using these achiral oligophenylenes and dibenzoyl tartaric acid as chiral auxiliaries in the achiral solvent, the same effect was observed [165].…”
Section: Diastereomers and Diastereomeric Recognitionsupporting
confidence: 70%
“…Finally, the formation of global homochirality assembly of BIC is supposed to be related to the strong supramolecular interactions between BIC aggregates and chiral 2-octanol, as well as the participation of the co-absorber in the assembly process. De Feyter’s group reported the chiral solvent and chiral auxiliary-biased formation of 2D enantiomeric assembly of achiral molecules2936, although with relatively low ee. Coincidently, the chiral solvent or chiral auxiliary is not indispensible for the formation of the assembly.…”
Section: Discussionmentioning
confidence: 99%
“…However, the nonlinear chirality amplification in molecular assemblies on solid surfaces consisting of achiral molecules has not been demonstrated. In addition, few examples have shown that 2D homochirality can be achieved by external means such as magnetic field and chiral solvent3233343536. For example, De Feyter et al have shown that the formation of 2D molecular rosettes can be biased towards being either right-handed or left-handed by using a chiral solvent36.…”
mentioning
confidence: 99%
“…the ability to steer the chirality of molecules or assemblies towards one specific handedness, have been performed [42,43]. Chiral symmetry on surfaces may be broken by the use of external agents in the form of a chiral solvent [44] or a magnetic field [45]. A related approach is the ''sergeants and soldiers'' effect where a homochiral seed induces a chiral response in target molecules as has been demonstrated in surface assemblies in a couple of instances [46][47][48].…”
Section: Introductionmentioning
confidence: 99%